Video Pembelajaran Fisika Sebagai Sumber Belajar Daring untuk Meningkatkan Motivasi Belajar Peserta Didik SMAN 9 Mataram di Masa Pandemi Covid-19 - Widianta, I Made Narta (Jurnal Paedagogy, 2021)
This study aims to increase students’ learning motivation during the Covid-19pandemic through physics learning videos. The research method used is qualitative research. This research was carried out during the odd semester of the 2020/2021 academic year at SMAN 9 Mataram for 35 students of class X MIA 3 through Google Classroom and Youtube. Data collection techniques using questionnaires, interviews and observations. Based on the results of the questionnaire analysis of students’ learning motivation, it was found that the application of physics learning videos as a learning resource caused students to have an average score of 54 (high category). Some of the students, namely 40% have learning motivation in the very high category, 49% in the high category, and 11% in the medium category. Thus, it can be concluded that the application of physics learning videos as a learning resource for students of class X MIA 3 SMAN 9 Mataram during the Covid-19pandemic can generate motivation to learn physics with the average student having motivation to learn in the high category.